2015
DOI: 10.1103/physrevb.91.045414
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and electrical resistance of highly disordered graphene

Abstract: Raman scattering (RS) spectra and current-voltage characteristics at room temperature were measured in six series of small samples fabricated by means of electron-beam lithography on the surface of a large size (5x5 mm) industrial monolayer graphene film. Samples were irradiated by different doses of C${}^+$ ion beam up to $10^{15}$ cm${}^{-2}$. It was observed that at the utmost degree of disorder, the Raman spectra lines disappear which is accompanied by the exponential increase of resistance and change in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…At large L D (small Φ), the ratio I D /I G increases with decreasing L D , passes through a maximum and then rapidly decreases. Such non-monotonic behavior is common for many experimental observations [5][6][7][8][9] and agrees with the theoretical model 13 based on the assumption that a single ion impact leads to the formation of a defect characterized by two length scales r S and r A (r A > r S ), which are the radii of two circular areas surrounding the defect (see insert in Fig. 5).…”
Section: Fig 3 (Color Online)supporting
confidence: 87%
“…At large L D (small Φ), the ratio I D /I G increases with decreasing L D , passes through a maximum and then rapidly decreases. Such non-monotonic behavior is common for many experimental observations [5][6][7][8][9] and agrees with the theoretical model 13 based on the assumption that a single ion impact leads to the formation of a defect characterized by two length scales r S and r A (r A > r S ), which are the radii of two circular areas surrounding the defect (see insert in Fig. 5).…”
Section: Fig 3 (Color Online)supporting
confidence: 87%
“…Due to the nature of our experiment, it was not possible to measure the electrical properties of the graphene itself because the particular level and type of disorder is achieved only after the deposition of Si, and its presence would, in turn, influence the measurement. However, there are numerous reports on the relation between I D /I G (or L D , n D ) and ρ (or sheet resistance, R S ) [32,33]. In stage 1, ρ ranges from ≈600 Ω of pristine CVD graphene to ≈ 20 kΩ [33].…”
Section: Resultsmentioning
confidence: 99%
“…For C + ions with M = 12 in atomic mass units (amu) and for Xe + ions (M = 131 amu) with E = 35 keV, k = 0.06-0.08 and 0.8 correspondingly [10]. The changes in the intensities of both D-and 2D-lines ID and I2D with increase of Nd in these samples were studied in [10][11][12]. It was shown that I2D continuously decreases, while ID first increases and then decreases, the maximal value is achieved at Nd ≈ 4x10 12 cm -2 , which corresponds to the mean distance between defects Ld ≈ (Nd) -1/2 ≈ 5 nm.…”
Section: Methodsmentioning
confidence: 99%